1993
DOI: 10.1037/0278-7393.19.4.851
|View full text |Cite
|
Sign up to set email alerts
|

The cue-familiarity heuristic in metacognition.

Abstract: Four experiments contrasted the cue-familiarity hypothesis of feeling-of-knowing judgments (FKJs) and tip-of-the-tongue feelings (TOTs) to the target-retrievability hypothesis. Familiarity of the cues was contrasted to memorability of the targets in a paired-associate design (e.g., A-B A-B, A-B A-B', A-B AD , A-B C-D), in which the number of repetitions of the cue A terms was dissociated from the memorability of the target B terms. Little support was found for the targetretrievability hypothesis, because in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
284
4
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(314 citation statements)
references
References 42 publications
(90 reference statements)
25
284
4
1
Order By: Relevance
“…This is consistent with the abundance of research that has established the importance of cues in metacognitive judgments (e.g. Metcalfe, Schwartz & Joaquim, 1993, Koriat & Lieblich, 1977, Schwartz & Smith, 1997.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the abundance of research that has established the importance of cues in metacognitive judgments (e.g. Metcalfe, Schwartz & Joaquim, 1993, Koriat & Lieblich, 1977, Schwartz & Smith, 1997.…”
Section: Discussionsupporting
confidence: 87%
“…Schwartz and Metcalfe also found that FOK ratings were not influenced by the degree of target encoding, whereas recall was influenced by this factor. Together, these findings represent dissociations between FOKs and actual knowing, and such dissociations have been obtained several times (see, e.g., Metcalfe et al, 1993;Reder & Ritter, 1992). Both tasks, knowing ratings and recall, apparently can be based on different sources of information, with FOKs being particularly sensitive to cue-based sources.…”
Section: Feelings Of Knowing and Cue-based Sources Of Informationmentioning
confidence: 99%
“…FOKs appear to be particularly sensitive to cue-based sources of information, but that is not always the case for other tasks, such as recall (see, e.g., Metcalfe, 1993;Metcalfe, Schwartz, & Joaquim, 1993;Reder & Ritter, 1992;Schwartz, 1994;Schwartz & Metcalfe, 1992). Schwartz and Metcalfe compared the effects of the degree of cue encoding (i.e., cue familiarization) and of the degree of target encoding on FOK ratings and cued recall.…”
Section: Feelings Of Knowing and Cue-based Sources Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Jacoby, and others, have made the case that implicit information may contribute to judgments such as fame (Jacoby, Kelley, Brown, & Jasechko, 1989), likeability, and social judgments (Bargh & Pietromonoco, 1982), and Koriat's case seems compelling: sometimes this kind of information is used when people are asked metacognitive judgments as well (Benjamin & Bjork, 1996). Indeed, studies such as those based on cue-familiarity (Metcalfe, Schwartz, & Joaquim, 1993;Reder & Ritter, 1992;Schwartz & Metcalfe, 1992), in which activation of the cue produces increases in people's feelings that they will know the target, even though the cue activation in no way increases the probability of target retrieval, lend support to this view, just as Koriat suggests. My reservation about the idea is not that I deny that implicit information can contribute to feelings of knowing, it is rather that I have slowly become convinced that these are not the only feeling states that are of importance in these judgments, and that, in some cases, people have access to the target itself.…”
mentioning
confidence: 99%